Road‐killed mammals provide insight into tick‐borne bacterial pathogen communities within urban habitats - Szekeres, Sándor; Docters van Leeuwen, Arieke; Tóth, Evelin; Majoros, Gábor; Sprong, Hein; Földvári, Gábor (Transboundary and emerging diseases, 2019)
Small‐ and medium‐sized mammals play an important role in the life cycle of tick‐borne pathogens in urban habitats. Our aim was to apply the general protocol, DAMA (documentation–assessment–monitoring–action), which is an integrated proposal to build a proactive capacity to understand, anticipate, and respond to the outcomes of accelerating environmental change. Here we tested whether road‐killed carcasses in urban areas are useful sources of tissue and parasite samples to investigate these species’ contribution to the epidemiology of vector‐borne diseases. We collected 29 road‐killed and 6 carcasses with different causes of mortality (23 northern white‐breasted hedgehogs and 12 from seven other mammal species) mainly from Budapest, Hungary. We used quantitative and conventional PCRs to determine pathogens in 90 collected tissues (52 from hedgehogs; 38 from other species) and 417 ticks that were only found on hedgehogs. Tissue samples revealed a wide range of bacteria including human zoonotic pathogens identified as Anaplasma phagocytophilum ecotype I, Borrelia afzelii, B. spielmanii, Borrelia miyamotoi, Rickettsia helvetica, and Bartonella species. Among the 23 collected hedgehog carcasses, 17 (74%) were infected with A. phagocytophilum, 6 (26%) with Borrelia burgdorferi s.l., 12 (52%) with R. helvetica, and 15 (65%) with Rickettsia sp. Furthermore, we report the first detection of Rickettsia sp. infection in European moles and lesser weasel and R. helvetica in stone marten. Through sequencing B. afzelii, R. helvetica, R. monacensis and A. phagocytophilum ecotype I were identified in the ticks removed from the carcasses. We showed that road‐killed urban mammal species are exposed to multiple tick‐borne pathogens but further studies have to clarify whether they, in fact, also have a role in their maintenance and spread. Our study also demonstrates that roadkill can be used in the risk assessment of potential human infection and in the implementation of the DAMA protocol.